Communicating the Annan plan : national identities, nationalism and interethnic negotiations in divided Cyprus - Avraamidou, Maria (Τμήμα Επικοινωνίας και Σποδών Διαδικτύου, Σχολή Επικοινωνίας και Μέσων Ενημέρωσης, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This thesis is interested in the relationship between media and national identies in divided Cyprus. It explores how the mainstream media constructed national identifications during a period of intense negotiations for peace settlement, known as “the Annan period”, and the ways in which individual Greek-Cypriots perceive that they used ideas of the nation and national identifications during the said period. In doing so the thesis critically examines the development of media constructed national identities vis-à-vis hegemonic tropes used to explain identity in Cyprus and in particular the Cyprocentrist-Hellenocentrist antagonism. The thesis approaches national identities as processes of “imagining” which are not static perceptions of who one is but may change or be modified in time. Over the last 40 years in Cyprus, the Greek-Cypriot and the Turkish-Cypriot communities have been locked in ongoing yet unsuccessful negotiations for a peace settlement. During most of the post-1974 period, the conflict has been a “calm” one. Focusing in particular on the Greek-Cypriot community, the thesis approaches negotiations as both routine and crisis news events. It foregrounds empirically how, in times of progress in the negotiations, the disputed settlement assumes a media epicentre of national identity discourses which draw and amplify more routinely prevalent national identity discourses. Based on a qualitative analysis and drawing on literature in nationalism and media studies, the thesis has uncovered the complex ways the “national” we was used during the period studied. It shows how media-projected norms of national conformity either closed or shifted the boundaries of we: on the one hand the us/ other binary homogenized opponents but also ourselves and on the other hand the boundaries of we opened up to include the other. The study confirms that neither Cyprocentrism nor Hellenocentrism, are static boundary formations of us and the other. By contrast, media discursive shifts between Hellenocentrism and Cyprocentrism, revealed that the confrontation between nation and state, as two antagonistic nationalistic codes, was not prominent in the said period. The study provides evidence however of exclusionary Cyprocentric constructions of identity premised primarily on uses of the state as a symbolic wall cementing the boundaries of we. In this regard, we explore constructions in the media of the Turkish-Cypriot community as an “absent/present” other as its interests and needs were tailored to project Greek-Cypriots’ own wishes. Yet, the thesis highlights the dislocation of the master dichotomy of us vs. other in media representations during the events which followed the relaxation of bizonal movement restrictions in April 2003. Building on Greek-Cypriots’ own accounts, the thesis concludes that, overall, national imaginings across and within communities become a “political prison” of the ethnic “other”, who becomes an absent/present “other”. But the community doing the “imagining” also tends to remain trapped within such conceptualisations: Participants of the study, about ten years after the referenda, understood the antagonism between Hellenocentrists and Cyprocentrists as being part of political elites’ own struggles for power still many explained how they could not go beyond nationally instigated perceptions about the other or the conflict. Yet this “imprisonment” is neither static nor should it be taken for granted, as there are instances during which otherwise powerful national identifications may break down and unravel in different directions. Additionally, the study shows a novel meta-analysis of nationalism and national identities from the perspective of individuals and in this context we provide evidence of an identity “fatigue” which problematizes further ideas on the naturalization of national identity. Overall, the thesis in answering the central research questions guiding the study, puts forward a claim and an assumption for further investigation. The claim manifested is that Cyprocentrism and Hellenocentrism were not necessarily antithetical during the Annan Period. The assumption is that it is possible in the future, for exclusionary and inclusionary tendencies within Cypriotism to become antagonistic. The exclusionary form tends to focus on civic identity to exclude other communities, not necessarily the Turkish-Cypriots who are in a way often included in this imagining as their presence fortifies the sovereignty of the state. On the other hand, inclusionary Cypriotism, despite emphasizing Cypriotness, remains tolerant towards others. Nevertheless, emphasis on the state should be addressed in other contexts as not merely related to a “civic” identity but also a cultural one.
Keywords: Cyprus conflict; Μedia analysis; Nationalism; National identities; Qualitative interviews